Comparison of the actual release dates of ascospores of the fungus Venturia inaequalis with those predicted by selected simulation models in an apple orchard in Central Poland - Sylwester Masny; Piotr Sobiczewski (Plant Protection Science, 2025)
The research was conducted in 2014-2017 in a multi-cultivar apple orchard in the Experimental Orchard of the National Institute of Horticultural Research (IO-PIB) in Dąbrowice near Skierniewice. To determine the actual Venturia inaequalis ascospores release dates, the Burkard spore trap installed in a plot of the McIntosh cv. that was not protected against apple scab was used. Monitoring of ascospore releases was carried out annually, starting from the appearance of numerous colouring (maturing) ascospores in the pseudothecia (usually in the second decade of March) and ending at the second half of June, usually about two weeks after the last release of these spores. The sums of ascospores detected on a given day and their proportion in all ascospores recorded during primary infections were calculated. The obtained results formed the basis for the analysis of forecast indications of the A-scab, Metos (Metos® Pessl Instruments), and RIMpro-Venturia models in connection with meteorological data from the Metos weather station installed in this orchard and to compare them with the actual release dates recorded by the Burkard spore trap. Depending on the year, significant differences were found in the number and intensity of V. inaequalis ascospore releases and in their beginning and end dates.